A re-evaluation of the frequency of CD8+ T cells specific for EBV in healthy virus carriers. - Tan, L; Gudgeon, N; Annels, N; Hansasuta, P; O'Callaghan, C; Rowland-Jones, S; Mcmichael, A; Rickinson, AB; Callan, M (1999)
EBV is a gammaherpesvirus that can establish both nonproductive (latent) and productive (lytic) infections within the cells of its host. Although T cell responses to EBV latent proteins have been well characterized, little is known about the importance of responses to lytic proteins in long term virus carriers. Here we have compared the frequencies of CD8+ T cells specific for EBV latent and lytic Ags in healthy virus carriers, using three techniques: limiting dilution analysis, enzyme-linked immunospot assay, and FACS staining with tetrameric MHC-peptide complexes. T cells specific for EBV lytic protein epitopes were readily detectable in all donors and were usually more abundant than those specific for latent epitopes. We infer that direct T cell control of viral replicative lesions is maintained in long term carriers of EBV and is an important component of the immune response to this virus. Estimates of CD8+ T cell frequencies varied considerably according to methodology; values obtained from MHC-peptide tetramer staining were, on the average, 4.4-fold higher than those obtained from enzyme-linked immunospot assays, which were, in turn, on the average, 5.3-fold higher than those obtained from limiting dilution analysis. Tetramer staining showed that as many as 5.5% circulating CD8+ T cells in a virus carrier were specific for a single EBV lytic protein epitope. Such values are much greater than previously imagined and illustrate how antigenic challenge from a persistent herpesvirus can influence the composition of the host's CD8+ T cell pool.